(untitled) (Research, Society and Development, 2023)
This article is based on the findings of a study driven by worries about the current state of education, which emphasizes the importance of developing children’s character in society. Character crises are ubiquitous, as seen by the increasingly popular attitude of the younger generation, which has lost touch with society’s manners or cultural values, pushing them to depart from established norms. The study objective is to offer a model for promoting children’s character education by enhancing the local wisdom of Sintuvu values in Binangga Village, Marawola Sub-district, Sigi Regency, Central Sulawesi, Indonesia. In this study, the FGD (Focus Group Discussion) and interviews are used in a field research paradigm or a field study to do qualitative research. The findings of this study show that sintuvu, as mutual-cooperation values for the Kaili community in Binangga Village, should be instilled in children through education, both official and informal schooling. As a result, parental involvement in education has a substantial impact on aspects of children’s character development beginning at a young age.